2018
DOI: 10.7717/peerj.6028
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive tissue-specific transcriptome profiling of pineapple (Ananas comosus) and building an eFP-browser for further study

Abstract: Pineapple is one of the most economically important tropical or subtropical fruit trees. However, few studies focus on the development of its unique collective fruit. In this study, we generated a genome-wide developmental transcriptomic profile of 14 different tissues of the collective fruit of the pineapple covering each of the three major fruit developmental stages. In total, 273 tissue-specific and 1,051 constitutively expressed genes were detected. We also performed gene co-expression analysis and 18 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The RT-qPCR results were consistent highly with our RNA-seq results (Fig. 8 A) and another published dataset of pineapple tissue-specific transcriptome 34 (Fig. 8 B), which provided solid proofs for the subsequent propose of ABCDE gene model (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The RT-qPCR results were consistent highly with our RNA-seq results (Fig. 8 A) and another published dataset of pineapple tissue-specific transcriptome 34 (Fig. 8 B), which provided solid proofs for the subsequent propose of ABCDE gene model (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The expression level of each gene was quantified as fragments per kilobase of exon model per million reads mapped (FPKM) values by featureCounts 65 . The third dataset from previous published study provided available expression matrix including different floral organs in transcripts per kilobase million (TPM) by Stringtie 34 , 66 . Two heat expression maps were generated by the Pheatmap package in R software using pre-treated FPKM values by log 2 transformation.…”
Section: Methodsmentioning
confidence: 99%
“…S4). In pineapple, genes co-expressed in bracts participate in plant-pathogen interactions and these genes may paly roles in plant defence [43]. Therefore, we can infer that the bract and shoot apex may function in plant defence.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that the divergence of tissue-speci c gene expression patterns modulates ion maintenance in tissues and improves salinity tolerance in Populus euphratica [42]. In pineapple (Ananas comosus), researchers detected 273 tissue-speci c genes, which provided a basis for the study of the genetic mechanisms that regulate fruit phenotypes [43]. Although studies of L. chinense tissues (leaves and petals) have been reported, tissue-speci c genes in L. chinense remain unknown, and this lack of knowledge impedes our understanding of tissue traits of this species [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This combined with other genomics tools, such as Electronic Fluorescent Pictograph (eFP) browsers [1] to help visualise where a gene is expressed, allows faster identi cation of gene function in different species. To date, eFP browsers have been successfully developed in plants such as Arabidopsis [1], tomato [2], strawberry [3], and pineapple [4].…”
Section: Introductionmentioning
confidence: 99%